Analysis of the Elastoplastic Response in the Torsion Test Applied to a Cylindrical Sample - Garcia-Herrera, C; Toro-Campos, S; Toro-Campos, S; Aranda-Acuna, P (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
This work presents an experimental and numerical analysis of the mechanical behavior of a fixed-end SAE 1045 steel cylindrical specimen during the torsion test. To this end, an iterative numerical-experimental methodology is firstly proposed to assess the material response in the tensile test using a large strain elastoplasticity-based model solved in the context of the finite element method. Then, a 3D numerical simulation of the deformation process of the torsion test is tackled with this previously characterized model that proves to be able to predict the development of a high and localized triaxial stress and strain fields caused by the presence of high levels of angular deformation. Finally, the obtained numerical results are analytically studied with the cylindrical components of the Green-Lagrange strain tensor and experimentally validated with the measurements of shear strains via Digital Image Correlation (DIC) and the corresponding torque - twist angle curve. © 2019 by the authors.